Pemberdayaan Guru Sekolah Dasar Dalam Penulisan Karya Tulis Ilmiah (KTI) Sebagai Upaya Peningkatan Kompetensi Guru Di Kecamatan Peranap - Fendrik, Muhammad; Antosa, Zariul; Witri, Gustimal; Permatasari, Silvia; Rizka, Mifta; Putra, Zetra Hainul; Zufriady, Zufriady (Unri Conference Series: Community Engagement, 2024)
Writing and publication of scientific papers (KTI) among teachers is still very concerning. This is indicated by the low productivity of teachers in writing and publishing scientific papers. This condition is in accordance with the statement of one of the teachers at the partner's place who stated that there are very few teachers who can write. Therefore, training is needed that can facilitate teachers to be able to improve their competence. This KTI writing training is very important for teachers because it can be a form of continuous professional development in promotion or class which can also improve teacher welfare. From the survey data before the training, participants had difficulty in compiling an appropriate research design and choosing the right analysis method. Participants were often unsure how to analyze the data and interpret the results. Participants often had difficulty in compiling logical conclusions and relevant recommendations. The results of the survey after the training showed a significant increase in understanding of the structure and objectives of scientific papers. Participants were able to present the background of the research more clearly and coherently after the training. Participants showed increased competence in compiling research designs and choosing the right analysis methods. Participants were more confident in analyzing data and interpreting results after participating in training for elementary school teachers in Peranap District, Indragiri Hulu Regency.